Pergeseran Ideologi dan Gerakan Islam: Dari Salafi, Fundamentalisme ke Islamisme - Rasuki; Nur Rahmad Yahya Wijaya (Kariman: Jurnal Pendidikan Keislaman, 2023)
This paper discusses the shifting ideology and Islamic movements that have occurred in several countries with Muslim-majority populations. By explaining some of the thoughts of Salafi and Fundamentalist ideologues such as Ibn Taimiyyah, Ibn Qayyim al-Jauziyah, Muhammad Ibn Abdul Wahab, apart from maintaining the purity of Islamic teachings, these two ideologies became the embryos for the brith of the ideology and movement of contemporary Islamism. Ideologists of Islamism such as Al-Maududi, Al-Banna responded to the dynamics of problems in Muslim society in general by voicing alternatives by proposing Islam as the final option by establishing an Islamic state and implementing Islamic law in the institution of an Islamic caliphate.